2011
DOI: 10.1901/jaba.2011.44-363
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Disruption in a Classroom Setting

Abstract: Substantial experimental evidence indicates that behavior reinforced on a denser schedule is more resistant to disruption than is behavior reinforced on a thinner schedule. The present experiment studied resistance to disruption in a natural educational environment. Responding during familiar activities was reinforced on a multiple variable-interval (VI) 7-s VI 30-s schedule for 6 participants with developmental disabilities. Resistance to disruption was measured by presenting a distracting item. Response rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 7 publications
1
38
0
1
Order By: Relevance
“…For example, Parry-Cruwys et al (2011) found greater resistance to distraction following richer reinforcement schedules in only five of six special-education students engaged in various classroom tasks, again suggesting the possibility of interaction with task-related intrinsic reinforcers. Relatedly, Sweeney et al (2014) found that between-subject variability in both pigeons and humans with intellectual disability was greater in conditions including analog sensory reinforcers.…”
Section: Discussionmentioning
confidence: 98%
“…For example, Parry-Cruwys et al (2011) found greater resistance to distraction following richer reinforcement schedules in only five of six special-education students engaged in various classroom tasks, again suggesting the possibility of interaction with task-related intrinsic reinforcers. Relatedly, Sweeney et al (2014) found that between-subject variability in both pigeons and humans with intellectual disability was greater in conditions including analog sensory reinforcers.…”
Section: Discussionmentioning
confidence: 98%
“…The basic experimental finding supporting the metaphor of behavioral momentum is that response classes associated with greater density of reinforcement are more persistent in the face of environmental distractors (Nevin, Mandell, & Atak, 1983). In a study with children with autism, Parry-Cruwys et al (2011) showed that a richer schedule of reinforcement (variable interval [VI] 7 s) of tokens or edibles produced a higher rate of task responding (e.g., puzzle building and block building) following distracters (e. g., videos) than a leaner schedule of reinforcement (VI 30 s). Presession pairing may work because the participant's cooperative behaviors inherent in the interactive presession activity are associated with a rich or dense schedule of reinforcement, and thus, cooperative behaviors in the presence of demands (i.e., distractors) may persist.…”
Section: Discussionmentioning
confidence: 99%
“…Following the war, this training model was replicated in business, industrial training, and in the classroom. 15 This type of systematic approach, although still common in the military, has not been applied in any meaningful way to surgical training, in spite of the fact that the two environments are analogous in the sense of consisting of definable tasks with severe consequences if unsuccessfully completed.…”
Section: Discussionmentioning
confidence: 99%